1977
DOI: 10.1093/ajcn/30.5.721
|View full text |Cite
|
Sign up to set email alerts
|

Level of education, level of income, and level of fatness in adults

Abstract: Socioeconomic status is systematically related to the level of fatness, and therefore the incidence of obesity, in a total community survey of nearly 5,000 adults. Among males with more than 12 years of schooling, the average thickness of 4 fatfolds is 10% greater, amounting to about 2 kg of total fat, than those with 8 years or less of education. In females, however, the opposite trend is observed, those in the higher educational group averaging 20% thinner fatfolds, or about 5.5 kg total fat, than females in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 7 publications
5
17
0
Order By: Relevance
“…15 However, these relationships are found more frequently in girls than in boys (as shown in this study). A number of studies have shown an inverse relationship between the level of parental education and overweight, 37,38 similar to the association between occupation of the father and overweight found in the present study. In contrast to this ®nding some studies report that higher parental income is associated with higher risk of child obesity.…”
Section: Discussionsupporting
confidence: 90%
“…15 However, these relationships are found more frequently in girls than in boys (as shown in this study). A number of studies have shown an inverse relationship between the level of parental education and overweight, 37,38 similar to the association between occupation of the father and overweight found in the present study. In contrast to this ®nding some studies report that higher parental income is associated with higher risk of child obesity.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the participants had a minimum of a high school diploma and a maximum of a bachelors degree and no established medical contraindications to exercise. These participation criteria were established to control for confounding variables including age, occupation and education which have been shown to be related to body composition and activity (8). The remaining variability associated with the confounding variables were statistically controlled with covariance procedures.…”
Section: Subjectsmentioning
confidence: 99%
“…Others have suggested rather significant heritability (20% to 30% of the variance) of habitual physical activity (18). Reference to possible racial differences are absent in these studies and do not address other confounders such as socioeconomic and cultural factors (8).…”
Section: Introductionmentioning
confidence: 98%
“…The problem of overweight is higher among females than males, blacks than whites, and the poor than the non-poor (Ross & Mirowsky, 1983). Garn et al (1977) explored level of education and income in relation to adult fatness. Males were more likely to be fatter with higher education and income, while females having higher education and income were more likely to be lean.…”
Section: The Social Ecology Of Obesitymentioning
confidence: 99%